Surveillance of rickettsial infections and whole genome analysis of a Rickettsia felis-like organism in Malaysia / Kho Kai Ling - Kho, Kai Ling (2017)
Rickettsioses are emerging zoonotic diseases which are often underdiagnosed due to nonspecific clinical manifestations, unavailability of appropriate diagnostic tools and a lack of awareness in developing countries. Information on the clinical, epidemiology and ecology of rickettsioses are scarce. The objectives of this study are to investigate selected cases of rickettsioses in febrile patients in University of Malaya Medical Center and to determine the seroprevalence of Malaysian populations against spotted fever group (SFG) rickettsiae. This study also aimed at determining the occurrences of rickettsiae in various arthropod and animal samples, and investigating the growth characteristics and genomic features of Rickettsia sp. TH2014, a rickettsial endosymbiont of C. felis orientis flea. This study describes the DNA detection of Rickettsia typhi, rickettsia closely related to Rickettsia raoultii and Rickettsia sp. RF2125 from the blood samples of four febrile patients and their clinical presentations. Analysis using indirect immunofluorescence assays showed significantly higher seropositivity rates to SFG Rickettsia amongst indigenous community [R. conorii (50.0 %) and R. felis (22.5 %)] and animal farm workers [R. conorii (13.8 %) and R. felis (16.1 %)] as compared to urban blood donors. Rickettsiae were detected up to 66.7 % in ticks and 96.9 % in fleas across different geographical locations. Sequence analyses of gltA, ompA and ompB partial genes revealed the identification of SFG rickettsiae closely related to R. raoultii, R. tamurae, R. conorii, R. heilongjiangensis, R. felis, Rickettsia sp. TCM1 and R. felis-like organism in ticks. Rickettsia closely related to R. raoultii and Rickettsia sp. RF2125 are the predominant species circulating in Peninsular Malaysia since they were detected in human, ticks, fleas and wildlife. Some potentially novel rickettsiae were also identified for future investigation. Transmission electron microscope analysis of Rickettsia sp. TH2014 growing in Aedes albopictus (C6/36) cells revealed spherical or elongated intracytosolic rickettsia which eventually caused the rupture of the host cells. The gltA (307 bp), ompB iv (793 bp) and 16S rRNA (1368 bp) of the strain exhibited 98.3 %, 94.8 % and 99.6 % similarity to R. felis type strain (URRWXCal2). The genome of Rickettsia sp. TH2014 was generated from Hi-seq sequencing and assembled with ABySS software to a depth of 954X coverage. The estimated genome size and GC content of the rickettsia are 1.37 Mb and 32.9 %, respectively. RAST analysis shows 1, 469 coding sequences, 32 tRNA genes and 3 rRNA genes. Genes associated with actin-based motility, adherence and invasion, T4SS secretion system and toxin-antitoxin system are annotated in the genome. Comparative whole-genome single nucleotide polymorphism analysis confirms the closely genetic relatedness of Rickettsia sp. TH2014 with R. felis type strain (URRWXCal2). In conclusion, based on the serological and molecular findings obtained in this study, rickettsioses should be considered as one of the differential diagnoses for unknown febrile illness in our local setting. The high detection rates of rickettsiae in a large collection of ticks and fleas in this study suggest potential exposure of local population to rickettsioses. The pathogenic role of Rickettsia sp. TH2014 in causing animal and human infections is yet to be investigated.